Padholm – en tæt bebygget jernalderboplads - Nørgaard Madsen, Jette Maria (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
In recent years, a large area surrounding Vonsild in South Jutland has been archaeologically excavated due to present-day expansion of Kolding. The excavation at Padholm resulted in 28 farmsteads and 144 three-aisled longhouses, dating primarily to the Early and Late Roman Iron Ages (50BP -350 AD). The 29 hectare large excavation site has provided new information and additions to earlier excavated Iron Age sites in the local area. Furthermore, several pollen analyses and dendrochronological dates have shed light on which crops were cultuvated by the inhabitants, the extent of deforestation at the time, and provided information about the surrounding landscape. Besides several clusters of settlements, a little structured settlement was excavated. Part of this settlement consisted of a small wetland area containing several pottery sherds from the Early Iron Age. For that reason, the wetland was examined in more detail. 36 14C-analyses from the different houses clarified the continuity of the settlement in the area. Furthermore, the radiocarbon dates have suggested some nuances to our typological knowledge of the three-aisledhouses in the early Iron Age. !e analyses suggest that the small houses with three and four sets of roof supporting posts date to the Early/Late Roman Iron Age. An analysis of the above information concludes that Padholm was composed of several social classes, and that agriculture was the main occupation.